The impacts of ODL during MCO@COVID-19 / Nor Hanim Abd Rahman - Abd Rahman, Nor Hanim (Unit Penerbitan JSKM, 2020)
For the past 5-months, COVID-19 is inevitably being part of our daily lives. New-norms are forced to be implemented in order to survive and move-on. This includes on how we seek knowledge, where globally all educational institutions are force to apply online-learning, e-learning or open-distance learning (ODL). WFH has also became a new-norm. Adjustments must be made to cater the new-norms, and it applies to all parties consist of students, lecturers, administrative and logistics. After 5 months, we can now study the positive and the negatives impacts of these new norms in our educational systems. For what I believe for every grey clouds, there is a silver lining!.